Antibiotic Resistance in Morganella morganii Species: Mechanisms, Prevalence and Clinical Implication - Anfal, Kara; Meriem, Elkolli; Naouel, Boussoualim (Anti-Infective Agents, 2024)
Morganella morganii, a member of the Enterobacteriaceae family, has gained increasing recognition as an important pathogen due to its multidrug resistance. In addition to its intrinsic resistance, it carries various resistance genes and mobile genetic elements, facilitating the spread of resistance genes. M. morganii develops its mechanisms of resistance through different genetic elements, and its pathogenicity is supported by several virulence factors. Its rate of resistance has attended high levels in a number of studies. The global prevalence of M. morganii- associated infections is observed with nosocomial and healthcare-associated infections. The spectrum of diseases caused by M. morganii is diverse, ranging from sepsis and urinary tract infections, abscess, purple urine bag syndrome, chorioamnionitis, and cellulitis to wound infections and bacteremia. Mortality rates associated with M. morganii infections remain high, emphasizing the need for effective treatment strategies. Thus, this article aimed to provide an overview of the evolving multidrug resistance, resistance genes, risk factors, spectrum diseases, and clinical significance of M. morganii, and the challenges associated with the diagnosis and treatment of M. morganii infections.
Keywords: mechanisms